Preventing clinically important deterioration with single-inhaler triple therapy in COPD. Issue 4 (3rd October 2018) - Naya, Ian; Compton, Chris; Ismaila, Afisi S.; Birk, Ruby; Brealey, Noushin; Tabberer, Maggie; Zhu, Chang-Qing; Lipson, David A.; Criner, Gerard
Clinically important deterioration (CID) is a novel composite end-point (lung function, health status, exacerbations) for assessing disease stability in patients with chronic obstructive pulmonary disease (COPD). We prospectively analysed CID in the FULFIL study. FULFIL (ClinicalTrials.gov NCT02345161; randomised, double-blind, double-dummy, multicentre study) compared 24 weeks of once daily, single-inhaler fluticasone furoate/umeclidinium/vilanterol (FF/UMEC/VI) 100/62.5/25 µg with twice daily budesonide/formoterol (BUD/FOR) 400/12 μg in patients aged ≥40 years with symptomatic advanced COPD (Global Initiative for Chronic Obstructive Lung Disease group D). A subset of patients received study treatment for up to 52 weeks. Time to first CID event was assessed over 24 and 52 weeks using two approaches for the health status component: St George's Respiratory Questionnaire and COPD assessment test. FF/UMEC/VI significantly reduced the risk of a first CID event by 47–52% versus BUD/FOR in the 24- and 52-week populations using both CID definitions (p<0.001). The median time to first CID event was ≥169 days and ≤31 days with FF/UMEC/VI and BUD/FOR, respectively. Only stable patients with no CID at 24 weeks demonstrated sustained clinically important improvements in lung function and health status at 52 weeks versus those who had experienced CID. Once daily, single-inhaler FF/UMEC/VI significantly reduced the risk of CID versus twice daily BUD/FOR with a five-fold longer period without deterioration. Fluticasone furoate/umeclidinium/vilanterol improves disease stability in COPD compared with budesonide/formoterol http://ow.ly/TaNY30loBa8